6‐TIPS‐β‐Cyclodextrin‐Modified Fe3O4 for Facile Enantioseparation of 1‐(1‐Naphthyl)ethylamine. Issue 24 (15th November 2016) - Wang, Lu; Liang, Xiang‐Yong; Ding, Li‐Sheng; Zhang, Sheng; Li, Bang‐Jing
Abstract: A new type of chiral magnetic nanoparticle was prepared from covalently linked magnetic nanoparticles (Fe3 O4 ) and heptakis‐(6‐O‐triisopropylsilyl)‐β‐cyclodextrin (6‐TIPS‐β‐CD). The resulting selectors (TIPS‐β‐CD‐MNPs) combined the good magnetic properties Fe3 O4 and efficient chiral recognition ability of 6‐TIPS‐β‐CD. The enantioselectivity of TIPS‐β‐CD‐MNPs towards 1‐(1‐naphthyl)ethylamine was six times higher than that of the parent β‐CD modified Fe3 O4 particles. Abstract : A great fit : A new kind of chiral magnetic nanoparticle (MNPs) with high magnetic saturation and high chiral recognition ability was successfully fabricated by using heptakis‐(6‐O‐triisopropylsilyl)‐β‐cyclodextrin (6‐TIPS‐β‐CD; see figure) as a chiral selector. Stereoselective absorption experiments by using 1‐(1‐naphthyl)ethylamine as a model for aromatic amines indicated that these TIPS‐β‐CD‐MNPs showed high chiral recognition ability.